GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 131309 species occurrences available in GBIF matching the query: TaxonKey: Tyto alba (Scopoli, 1769). The dataset includes 131309 records from 373 constituent datasets: 41 records from CSUC Vertebrate Collection. 2 records from PlutoF platform observations. 42 records from rmca-albertine-rift-birds. 13 records from Animal Sound Archive. 50 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 5 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 10 records from National Biodiversity Data Bank. Observation records, 1900-2014. 106 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 13 records from University of Ghent - Zoology Museum - Vertebratacollectie. 15 records from Plan de vertebrados de la Patagonia. 10 records from KUBI Ornithology Tissue Collection. 33 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 815 records from Bird Atlas 2007 - 2011. 17 records from CHAS Ornithology. 1 records from Local BioBlitz Challenge 2013. 166 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 3763 records from Inventario Español de Especies Terrestres (MAGRAMA). 6 records from TTRS Ornithology. 7 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 5 records from The atlas of breeding birds in Małopolska. 1 records from MVZ Hildebrand Collection (Arctos). 80 records from Donnees ONF Faune-Flore-Fonge. 69 records from Bird Ringing Centre in Sweden (NRM). 194 records from iNaturalist research-grade observations. 95 records from Aranzadi Ringing Scheme (bird ring-recovery data). 1 records from Birdrace-Brut-Wetteraukreis. 1 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 1 records from Birdrace-Enger_am_Spektiv-Herford. 1 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 1 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 1 records from Birdrace-Halsbandschnäpper-Stuttgart. 1 records from Birdrace-Die_Ornithomaten-Herford. 1 records from Sudeniederung (Amt Neuhaus). 1 records from BIRDRACE Cuxland - Schwenke Geo Consult. 2 records from BIRDRACE Havelland. 1 records from BIRDRACE federleser. 1 records from BIRDRACE Duckehühnchen. 1 records from BIRDRACE The early birds. 1 records from BIRDRACE Gütersloher Gimpel. 1 records from BIRDRACE Linumer Luchschleicher. 1 records from Ireland's BioBlitz 2012. 1 records from Collection Aves - PUM. 8 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 1 records from Naturschutzgebiet Lüneburger Heide. 4 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 1 records from Tissues Specimens. 2912 records from First Bird Atlas. 1547 records from OEH Atlas of NSW Wildlife. 248 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 29 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 2 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 6 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 3 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 8007 records from Southern African Bird Atlas Project. 1 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 557 records from natagora-earlybirds. 658 records from Fauna Atlas N.T.. 11 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 87 records from Lund Museum of Zoology (MZLU). 2 records from Bird Monitoring Data. 16 records from UAM Bird Collection (Arctos). 17 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 1 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 1 records from Birdrace-federleser-Herford. 1 records from Birdrace-Buteo1_DO-Dortmund. 1 records from Birdrace-Die_Paradiesvögel-Herford. 1 records from Birdrace-ImmerWiederhopf-Lörrach. 3 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 10 records from Zoology (Museum of Evolution - Uppsala). 12 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 13 records from Perot Museum of Nature and Science. 29 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 10 records from UAFMC Birds. 11 records from Clare Biological Records Centre dataset. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 6 records from Eggs Specimen. 42 records from CCBER Ornithology Collection. 300 records from Museum of Comparative Zoology, Harvard University. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 60906 records from EOD - eBird Observation Dataset. 4 records from Birds collection of Yamashina Institute for Ornithology. 12 records from Musée Vert ornithology collection. 13 records from University of California Museum of Paleontology. 477 records from NMNH occurrence DwC-A. 1 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 2 records from BIRDRACE RennVögel Münsterland. 1 records from Birdrace-Team_Havelland-Havelland. 1 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 3 records from MVZ Bird Observations (Arctos). 3732 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 2 records from BIRDRACE Gätkes Erben. 1 records from BIRDRACE Upupa epöpse. 1 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 1 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 1 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 1 records from BIRDRACE Die Borner. 1 records from BIRDRACE nabu-rhein-main.de. 1 records from BIRDRACE Professorenteam. 821 records from naturgucker. 69 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 205 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 2 records from Axel W. Erikssons African Birdcollection at Vänersborg Museum. 171 records from Western Australian Museum provider for OZCAM. 23 records from The avian collection at the Natural History Museum, Oslo, Norway. 52 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 107 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 75 records from DMNS Bird Collection (Arctos). 1 records from Colección Ornitológica de la Universidad Industrial de Santander. 4 records from HSU Wildlife Eggs and Nests. 67 records from CRCM Vertebrate Collection. 100 records from NCSM Birds Collection. 9 records from Tasmanian Museum and Art Gallery provider for OZCAM. 3 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 28 records from NYSM Birds. 1 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 1812 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 43 records from Census of the animals of Benin. 1 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 1 records from Birdrace-Uhulogen-Lippe. 1 records from Birdrace-Herford-Birder-Herford. 1 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 1 records from Birdrace_Schräge_Vögel-Herford. 1 records from Birdrace-Die_Nachtigallen-Herford. 1 records from Birdrace-The_early-Birds-Minden/Lübbecke. 1 records from BIRDRACE Nord-Seh-Team. 1 records from BIRDRACE Wannacks Topti(c)ker. 2 records from BIRDRACE Pody und Co. 1 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 2 records from BIRDRACE Raumpatrouille Oriolus. 1 records from BIRDRACE Ave Goettingen!. 1 records from BIRDRACE Die UHULOGEN. 1 records from BIRDRACE VIE will rock you!. 2 records from BIRDRACE Dithmarscher Deichhühner. 1 records from BIRDRACE Kingfisher. 2 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 1 records from National Trust - Hatfield Forest species data held by The National Trust.. 48 records from UMZC Zoological Specimens. 25 records from Tullie House Museum - Tullie House Museum Natural History Collections.. 190 records from LACM Vertebrate Collection. 5 records from SysTax - Zoological Collections. 213 records from Merseyside BioBank - North Merseyside Birds (verified). 38 records from Merseyside BioBank - North Merseyside Birds (unverified). 380 records from Field Museum of Natural History (Zoology) Bird Collection. 229 records from Museum Victoria provider for OZCAM. 26 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 2 records from UCM Bird Eggs/Nests Collection (Arctos). 1315 records from Historical Bird Atlas. 31 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 1963 records from BirdLife Australia, Birdata. 2 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 240 records from CAS Ornithology (ORN). 1 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 2 records from Estonian Museum of Natural History. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 13 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 2 records from Literature based species occurrence data of birds of North-East India. 1 records from Birdrace_Die_Borner-Viersen. 1 records from Birdrace-Team_BO-bachter-Bochum. 1 records from Birdrace_turbine_untersee-Konstanz. 1 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 1 records from Birdrace-Die_Vogelscheuchen-Herford. 1 records from Upper Silesian Museum, Bird Collection. 2 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 1 records from BIRDRACE Turbine Untersee. 1 records from BIRDRACE Die Ziegeneier. 1 records from BIRDRACE SchrägeVögel. 1 records from BIRDRACE TEAM BO-BACHTER. 1 records from BIRDRACE Lohmanns Öömi-Studenten. 1 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 1 records from BIRDRACE Die Otzberger. 1 records from BIRDRACE Die Göttinger Sozialbrachvögel. 1 records from BIRDRACE Griffin Wood Warblers. 1 records from BIRDRACE Brut. 1 records from BIRDRACE Birding Bentheim. 1 records from BIRDRACE Herford Birders. 1 records from BIRDRACE Resopal-Darmstadt-Dieburg. 1 records from BIRDRACE Ornis im Einsatz. 3 records from Schmidt Museum of Natural History_Birds. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tytonidae. 2 records from ZFMK AMIBIO. 4 records from Baillon Collection. 109 records from SBMNH Vertebrate Zoology. 23 records from Natural History Museum Rotterdam (NL) - Chordata collection. 17 records from Collection Ornithologie - ZSRO. 58 records from Macaulay Library Audio and Video Collection. 3 records from Avifauna de la laguna Madre de Tamaulipas. 2 records from Collection Anatomie Histologie - SMF. 1 records from Ontario Breeding Bird Atlas 2001-2005. 198 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 21 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 3 records from NBM birds. 110 records from SDNHM Birds Collection. 4 records from Bird Collection. 10 records from University of Alberta Ornithology Collection (UAMZ). 4 records from Bird tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 120 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 684 records from Banc de dades de biodiversitat de Catalunya-VerteCat. 2 records from IndOBIS, Indian Ocean Node of OBIS. 33 records from Point Reyes Bird Observatory - Point Counts. 5 records from MZFC/Coleccion de Aves. 7 records from UCM Bird Collection (Arctos). 1 records from Überall ist Wunderland. 1 records from Gemeinde Sursee. 1 records from Leegmoor (Moormerland/Leer). 1 records from Pilstingermoos. 1 records from Südwestlich der Parkwiesen. 1 records from Landesweite NABU-Vogelrallye. 1 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 1 records from Birdrace-Raumpatrouille_Oriolus-Münster. 644 records from WFVZ Bird Collections. 91 records from PSM Vertebrates Collection. 6 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 21 records from Northern Territory Museum and Art Gallery provider for OZCAM. 2 records from Estación Experimental de Zonas Áridas (CSIC) EEZA - Aves. 5 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 1 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 926 records from NatureServe Network Species Occurrence Data. 1 records from Riqueza específica, distribución y abundancia de aves acuáticas en la ensenada de La Paz, Baja California Sur, México. 2 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 2 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 5 records from Ireland's BioBlitz. 14 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 1 records from Ibaraki Nature Museum, Birds collection. 207 records from RBINS collections. 28 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 25 records from Birds of Ireland. 3 records from Bird Observational Records. 1361 records from Great Backyard Bird Count. 222 records from UWBM Ornithology Collection. 41 records from Royal British Columbia Museum. 20 records from Ontario Nest Records. 2 records from Paleobiology Database. 33 records from Database Schema for UC Davis Wildlife museum. 30 records from CNAV/Coleccion Nacional de Aves. 23 records from MMNH Museum Bird Collection. 450 records from Israel Nature and Parks Authority. 34 records from UCLA Donald R. Dickey Bird and Mammal Collection. 24 records from Bird Collection. 1339 records from Eremaea. 1 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 1 records from Birdrace_MarschPIeper_Pinneberg. 5358 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008). 181 records from Natural History Museum (London) Collection Specimens. 2 records from Collection Ornithologie - SNSD. 4 records from Ontario Breeding Bird Atlas 1981-1985. 7697 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 143 records from Bird specimens. 40 records from Birds Specimens. 1 records from IIAPPoa. 161 records from Biologiezentrum Linz. 115 records from ORN. 87 records from Aves MZS. 21 records from Staffordshire Ecological Record - SER Site-based Surveys. 1 records from Frauenholz (Holzmaden). 1 records from Gemeindegebiet Weikendorf (Marchfeld). 76 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 1 records from Naturpark Drömling. 56 records from Collection Aves (spirit preserved) SMF. 44 records from UAZ Bird Collection. 107 records from DATAVES. 10 records from The Scottish Ornithologists' Club - Fife breeding bird tetrad atlas 1991-99. 46 records from HSU Wildlife Birds. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Guaminí (Carrique, octubre 1999). 65 records from Bernice P. Bishop Museum. 5 records from Observaciones de Especies Silvestres (by Charif Tala). 1 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 7 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 3650 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 6 records from Hare Survey of Ireland 06/07. 3 records from CHAS Oology. 1 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 1 records from Avifauna de la reserva de la biosfera El Cielo, Tamaulipas, México. 697 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 28 records from RSPB - RSPB Reserves breeding bird surveys. 20 records from Canadian Museum of Nature Bird Collection. 25 records from Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN. 41 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 1 records from Individual Sightings. 7 records from UC Davis Department of Anthropology Museum. 8 records from Museum of Zoology, University of Navarra. 29 records from UNSM Vertebrate Specimens. 3 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 1 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 1 records from Faberpark (Nürnberg/Stein). 1 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from Bergkamen- Bergehalde Großes Holz. 1 records from Birdrace-Nord_Seh_Team-Nordfriesland. 1 records from Birdrace-Alte_Socken-Cuxhaven. 15 records from MLZ Bird Collection (Arctos). 135 records from The First Atlas of Wintering Birds in Britain and Ireland: 1981/82-1983/84.. 14 records from Greater Manchester Ecology Unit - Distribution of Species of Conservation Interest in Greater Manchester. 86 records from New Mexico Biodiversity Collections Consortium database. 243 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 7 records from Biological and palaeontological collection and observation data MNHNL. 268 records from BioGIS - Birds - INPA database. 17 records from Colección Nacional de Ornitología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 6 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 138 records from Queensland Museum provider for OZCAM. 153 records from CM Birds Collection. 36 records from ArtenFinder. 498 records from The First Atlas of Breeding Birds in Britain and Ireland: 1968-1972.. 1 records from CMC_ornithology_GRC. 1 records from Fieldjournal.org observation database. 41 records from Norwegian Species Observation Service. 4 records from MSB Host Collection (Arctos). 1 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 23 records from Fundación Miguel Lillo - Colección Ornitológica. 1 records from Natural History Museum, University of Tartu. 5 records from Coleccion de sonidos ambientales. 91 records from Collection Aves (bird skeletons) SMF. 172 records from Collection Aves (bird skins) SMF. 1 records from DOF 2001-2006. 1 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 33 records from MVZ Egg and Nest Collection (Arctos). 2 records from National Trust - Sutton Hoo species data held by The National Trust.. 3 records from UWYMV Bird Collection (Arctos). 30 records from EcoRecord - Bird records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1801 records from SAFRING. 74 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 723 records from Staffordshire Ecological Record - SER Species-based Surveys. 10 records from Tiira information service. 57 records from DMNH Birds. 6 records from DMNS Egg Collection (Arctos). 14 records from Queen Victoria Museum Art Gallery provider for OZCAM. 4 records from Instituto de ciencias naturales. 12 records from Colección nacional de zoología. 6 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 674 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 76 records from Sheffield Bird Study Group - Sheffield Bird Study Group (Yorkshire records). 2841 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009. 742 records from AMNH Bird Collection. 2 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 2 records from Colección Ornitológica de la Universidad del Valle. 2 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 2 records from National Trust - Ickworth species data held by The National Trust.. 8 records from Geographically tagged INSDC sequences. 49 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 1 records from Aves Tanzanian collection at the Natural History Museum of Denmark (SNM). 53 records from Cowan Tetrapod Collection - Birds. 6 records from WNMU Bird Collection (Arctos). 36 records from Aves Collection of Institute of Systematics and Evolution of Animals. 1 records from Ájtte. 435 records from Australian Museum provider for OZCAM. 230 records from The Second Atlas of Breeding Birds in Britain and Ireland: 1988-1991. 42 records from Royal Museum of Central Africa - Albertian Rift Birds (ENBI wp13). 255 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 36 records from UTEP Vertebrates. 153 records from UMMZ Birds Collection. 1 records from Seil Natural History Group - SNHG Biological Records Dataset. 11 records from IICT Colecção Zoológica. 102 records from MSB Bird Collection (Arctos). 304 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 35 records from Garden Bird Surveys. 80 records from Données ONF Faune-Flore-FOnge. 6 records from Hare Survey of Ireland 06/07 - Non Hare records. 1 records from Caire-Chabrand Collection. 209 records from Ditsong Museum. 11 records from National System of Protected Areas in Poland - Animals. 2 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 10 records from National Trust - Heigham Holmes species data held by The National Trust. 224 records from MVZ Bird Collection (Arctos). 93 records from KUBI Ornithology Collection. 3 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 3 records from Anymals+plants - Citizen Science Data. 43 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 1 records from Kieppi bird collection. 3 records from The Bat Conservation Trust - The BCT/MTUK Bats & Roadside Mammals Survey. 3 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 57 records from CUMV Bird Collection (Arctos). 276 records from South Australian Museum Australia provider for OZCAM. 4 records from ISU Birds. 19 records from Bird Collection of Museum and Institute of Zoology PAS.
Keywords: GBIF; biodiversity; species occurrences